2021
DOI: 10.18632/aging.203400
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a three-miRNA signature as a prognostic model for colorectal cancer through bioinformatics analysis

Abstract: Background: Identification of more promising microRNAs (miRNAs) are being extensively studied with respect to colorectal cancer (CRC), since CRC is the leading cause of cancer deaths and most common malignant tumors worldwide. A series of colon cancer (CCa) samples from The Cancer Genome Atlas (TCGA) were analyzed to provide a new perspective into this field. Methods: The expression of miRNAs, mRNAs and the clinical data of 437 CRC patients were downloaded from the TCGA database. The survival-related different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…For instance, Li et al assessed the prognostic value of methylation regions in CRC and detected four differentially methylated regions, namely MUC12, TBX20, CHN2, and B3GNT7, as potential prognostic indicators for CRC and created a prognostic prediction score on their basis 34 . Moreover, many other reports have focused on transcriptional-level analysis, including research on mRNAs, long non-coding RNAs (lncRNAs), or miRNAs 35 37 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Li et al assessed the prognostic value of methylation regions in CRC and detected four differentially methylated regions, namely MUC12, TBX20, CHN2, and B3GNT7, as potential prognostic indicators for CRC and created a prognostic prediction score on their basis 34 . Moreover, many other reports have focused on transcriptional-level analysis, including research on mRNAs, long non-coding RNAs (lncRNAs), or miRNAs 35 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The 14 miRNAs were correlated with the prognosis of patients with carcinoma of colon. However, other researchers have reported that upregulation of hsa-miR-194-3p was associated with the early T-stages [41].Studies have shown that high levels of mir-21-3p are associated with short survival time, poor prognosis, pathological features and positive lymph nodes [42]. Its overexpression in breast tumors is a sign of disease deterioration.…”
Section: Discussionmentioning
confidence: 98%
“…The real-time quantitative PCR (qPCR) was conducted as previous report [ 30 ]. Extracted total RNA from tissues and cell lines by Triazole (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%